2022
DOI: 10.1038/s41598-022-10773-0
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on strength improvement of expansive subgrades by polypropylene fibers and geogrid reinforcement

Abstract: The rapid development of infrastructure often encounters the loose subgrades and is becoming difficult to carry to construction activities. Numerous counteracting methods are developed to control the swelling-shrinkage behavior of the expansive subgrades. The mechanical stabilization of the expansive subgrades by reinforcing with the polypropylene fiber and geogrid is sustainable. Geogrids and polypropylene fibers have been used extensively to strengthen the expansive subgrade and foundations as individuals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 51 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Microstructural analysis involves examining aspects such as the size and shape of apertures, the arrangement of ribs, and the material composition of the geogrid. These factors in uence how well the geogrid interacts with the soil, providing stability, reinforcement, and drainage as needed [51]. Physical property analysis delves into the geogrid's mechanical behaviour, including its tensile strength, exural rigidity, puncture resistance, interface friction, and water permeability.…”
Section: Ftir Characterizationmentioning
confidence: 99%
“…Microstructural analysis involves examining aspects such as the size and shape of apertures, the arrangement of ribs, and the material composition of the geogrid. These factors in uence how well the geogrid interacts with the soil, providing stability, reinforcement, and drainage as needed [51]. Physical property analysis delves into the geogrid's mechanical behaviour, including its tensile strength, exural rigidity, puncture resistance, interface friction, and water permeability.…”
Section: Ftir Characterizationmentioning
confidence: 99%
“…Upon reaching a certain threshold of shear displacement, the interfacial shear stress stabilized. TIWARI and SATYAM's [18] large-scale direct shear and unconfined compressive strength tests on the interaction at the interface between the subgrade, polypropylene fibers, triaxial geogrids, and biaxial geogrids revealed that the shear strength of the reinforced subgrade increased by 177% with the addition of bi/triaxial geogrids and polypropylene fibers. CEN et al [19] developed a large-scale composite shear test apparatus to study the shear behavior of various geomembrane interfaces, observing higher peak shear stresses and shear displacements on textured geomembrane-soil interfaces compared to smooth ones.…”
Section: Introductionmentioning
confidence: 99%
“…While it has been acknowledged that different laboratory experiments can effectively replicate the behavior of soil and geogrids in specific components of embankments [15], a significant portion of these tests has been carried out using the direct shear apparatus [16]. These experiments encompass diverse aspects, such as different soil types, particle sizes, soil densities, and moisture contents [17][18][19][20][21], as well as variations in the type of geogrids, aperture sizes, and shapes [22][23][24][25]. An important parameter found to increase the reinforcement effect is the number of geogrid-reinforcement layers [26].…”
Section: Introductionmentioning
confidence: 99%